Asystole in a young child with tetrahydrocannabinol overdose: a case report and review of literature - Masilamani, Mats Steffi Jennifer; Leff, Rebecca; Kawai, Yu (Frontiers in Toxicology, 2024)
Introduction The association between Δ8-tetrahydrocannabinol (THC) and cardiac dysrhythmia has not been well described in children. Asystole, while consistent with reports of severe bradycardia and apnea in children, is uncommonly described in the current literature. We present the first pediatric case of asystole and apnea following THC ingestion. Case A 7-year-old male presented to the emergency department (ED) after his mother noticed he was lethargic 3–4 h after accidental ingestion of five 15 mg (total of 75 mg) Δ8-THC gummies. Upon arrival, he was vitally stable and well-appearing. He received maintenance intravenous fluids. Approximately 7 h after initial ingestion, he experienced a >15-s episode of asystole and apnea on telemetry requiring sternal rub to awaken. This was followed by bradycardia (60 beats per minute range) which resolved with 0.1 mg glycopyrrolate. He was admitted to the PICU, drowsy but arousable with stable vitals. After an uneventful 24-h (post-ingestion) PICU observation, he was discharged home in stable condition. Discussion To our knowledge, this is the first reported pediatric case of THC-induced asystole. The etiology of asystole may be attributed to direct vagal stimulation of THC or respiratory depression. The typical recommended observation time after potential toxicity is 3–6 h after children have returned to their physiological and behavioral baseline. Our patient was clinically stable with no concern for respiratory depression or cardiac dysrhythmia yet experienced an asystolic pause with apnea 7 h after initial ingestion. Conclusion Our case demonstrates that asystole and apnea may occur in pediatric patients following large THC ingestions and those symptoms can appear late outside of the currently recommended observation period.